The actions of a new β-adrenoceptor blocking drug, ICI 66082, on the rabbit papillary muscle and on the dog heart - Harry, J.D. (1974)
1 The actions of 4-(2-hydroxy-3-isopropylaminopropoxy) phenyl acetamide (ICI 66082), a new β-adrenoceptor blocking drug, on the twitch response of the isolated papillary muscle of the rabbit and on dP/dt max and free heart rate of a denervated dog heart preparation, are described. 2 ICI 66082 (up to 1 mg/ml) did not produce any depression of the twitch response of the rabbit papillary muscle. ICI 66082 antagonized the action of isoprenaline on this preparation at a concentration of 0.01 μg/ml. 3 ICI 66082 (0.5-1.0 mg/kg intravenously) reduced the control value of dP/dt max in four dog preparations by a mean value of 529 mmHg/s (s.e. mean ± 139 mm Hg/s), with no significant change in free heart rate. Antagonism of the effect of isoprenaline on dP/dt max and on free heart rate was demonstrated with ICI 66082 (0.1 mg/kg). 4 ICI 66082 (1.0-1.5 mg/kg) produced no significant changes in dP/dt max or in free heart rate in four dogs pretreated with reserpine. A significant reduction (16% of the control value) in dP/dt max was observed with ICI 66082 at a high dose of 40-50 mg/kg. 5 It is concluded that ICI 66082 is a competitive antagonist against the actions of isoprenaline on cardiac muscle, has no negative inotropic action (unless the dose exceeds 40 mg/kg) and lacks intrinsic sympathomimetic activity.